The new carbon architecture : building to cool the climate - King, Bruce (Structural engineer) (New Society Publishers, 2017)
Like never before in history, buildings can become part of the climate solution. With biomimicry and innovation, we can pull huge amounts of carbon out of the atmosphere and lock it up as walls, roofs, foundations, and insulation. We can literally make buildings out of sky with a massive positive impact. This book presents a paradigm-shifting tour of the innovations in architecture and construction that are making this happen. Office towers built from advanced wood products; affordable low-carbon concrete alternatives; plastic cleaned from the oceans and turned into building blocks. We can even grow insulation and bricks! This book will fire the imagination of architects, engineers, builders, policy makers, and everyone else captivated by the possibility of architecture that heals the climate and produces safer, healthier, and more beautiful buildings.